Diplomasi Indonesia-Filipina dalam Memperkuat Kesatuan ASEAN dan Tantangan Politik Regional - Satrio Ramadhan; Elly Nurlia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article explores the strategic role of bilateral diplomacy between Indonesia and the Philippines in strengthening ASEAN unity amidst regional political challenges. Using a qualitative research approach with descriptive analysis, it examines how diplomatic cooperation on security, conflict resolution, and economic collaboration has contributed to regional stability and integration. The study highlights Indonesia's role in mediating internal conflicts in the Philippines and joint efforts in maritime security. Despite geopolitical tensions and domestic political changes, the bilateral relationship remains crucial for ASEAN's resilience and cohesion. The findings emphasize the importance of sustained diplomatic engagement for fostering regional solidarity and addressing emerging global challenges.